Two new pyranoxanthones from the stem bark of Calophyllum pseudomolle P.F. Stevens - Mulyadi Tanjung (Taylor & Francis, 2020)
Two new pyranoxanthones, calotetrapterins D (1) and E (2), were isolated from the stem bark of Calophyllum pseudomolle P.F. Stevens along with α-mangostin (3). The structures of compounds 1–2 were determined based on 1D NMR (1H, 13C) and 2D NMR (HMQC, HMBC), as well as HRESIMS spectroscopic analysis. Compounds 1–2 showed moderate activity against HeLa and murine leukaemia P-388 cells.